Endoscopically Placed Rectourethral Guidewire Facilitates the Reconstruction of Anus in Children with Anorectal Malformations: A Case Report - Stenström, Pernilla; Anderberg, Magnus; Kockum, Christina Clementson; Arnbjornsson, Einar (European Journal of Pediatric Surgery Reports, 2013)
The aim of this report is to present a technical detail of use in the management of an anorectal malformation (ARM). A boy with ARM and a fistula to the urethra was operated on with a posterior sagittal anorectoplasty (PSARP). Before the PSARP operation, a videoendoscopy was performed through the distal stoma down to the distal end of the rectum. The rectourethral fistula was identified and a guidewire was passed through the endoscope, through the fistula, and out through the urethra. The endoscopically placed rectourethral guidewire was used as a landmark and facilitated the PSARP operation.
Keywords: anorectal malformation; posterior sagittal anorectoplasty; newborns; endoscopy; rectourethral fistula